KONVERGENSI MEDIA DI ERA DIGITAL (EKSPLOITASI MEDIA KOMUNIKASI DALAM PROSES BELAJAR MENGAJAR DI ERA DIGITAL) - Sri Sediyaningsih (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2018)
The issuance of the Law No. 20 of 2003 concerning the National Educational System further strengthened the existence of the Distance Education System which was regulated further through Ministry of Education and Culture Regulation No. 24 of 2012 and Ministry of Education and Culture Regulation No. 109 of 2013. The issuance of both regulations also provided opportunities for public and private higher education institutions to administer distance higher education platform, so that universities in Indonesia had many opportunities to provide their learning services through distance learning. Accompanied by technological advancements, the distance learning process got the opportunity to meet the community’s expectations for the reach of higher education. Serious management was needed in managing the teaching and learning process in distance education. Each media had its own characteristics and capabilities in reaching its audience. Therefore, it was necessary to observe what media that should be used in the teaching and learning process. To answer this problem, through ethnomethodology methods based on constructivist thinking, and based on the theory of diffusion-innovation, media interpersonal communication, and decontextualisation of messages, the results of this study provided an overview of how media selection and media utilization in the teaching and learning process in the distance education method.